Wild grasses as the reservoirs of infection of rust species for winter soft wheat in the Northern CaucasusWild grasses as the reservoirs of infection of rust species for winter soft wheat in the Northern Caucasus - E. I. Gultyaeva; L. A. Bespalova; I. B. Ablova; E. L. Shaydayuk; Zh. N. Khudokormova; D. R. Yakovleva; Yu. A. Titova (Вавиловский журнал генетики и селекции)
Common winter wheat is the main grain crop cultivated in the North Caucasus. Rust disease damage is one of the factors limiting wheat productivity. There are three species of rust in the region: leaf (Puccinia triticina), stem (P. graminis) and stripe rust (P. striiformis), and their significance varies from year to year. The most common is leaf rust, but in the last decade the frequency of its epiphytotic development has significantly decreased. At the same time, an increase in the harmfulness of stripe rust (P. striiformis) is noted. Stem rust in the region is mainly absent or observed at the end of the wheat growing season to a weak degree. Only in some years with favorable weather conditions its mass development is noted on susceptible cultivars. It is believed that the sources of infection with rust species in the North Caucasus are infested soft wheat crops, wild-growing cereals and exodemic infection carried by air currents from adjacent territories. In the North Caucasus, forage and wild grasses are affected by Puccinia species almost every year. Depending on weather conditions, the symptom expression is noted from late September to December and then from late February to May–June. Potentially, an autumn infection on grasses can serve as a source for infection of winter soft wheat cultivars sown in October. The purpose of these studies is to characterize the virulence of P. triticina, P. graminis, P. striiformis on wild cereals and to assess the specialization of causative agents to winter wheat in the North Caucasus. Infectious material represented by leaves with urediniopustules of leaf, stem and stripe rusts was collected from wild cereals (Poa spp., Bromus spp.) in the Krasnodar Territory in October–November 2019. Uredinium material from P. triticina, P. striiformis, and P. graminis was propagated and cloned. Monopustular Puccinia spp. isolates were used for virulence genetics analysis. In experiments to study the specialization of rust species from wild-growing cereals on common wheat, 12 winter cultivars were used (Grom, Tanya, Yuka, Tabor, Bezostaya 100, Yubileynaya 100, Vekha, Vassa, Alekseich, Stan, Gurt, Bagrat). These cultivars are widely cultivated in the North Caucasus region and are characterized by varying degrees of resistance to rust. Additionally, wheat material was inoculated with Krasnodar populations of P. triticina, P. striiformis, P. graminis from common wheat. In the virulence analysis of P. triticina on cereal grasses, four phenotypes (races) were identified: MCTKH (30 %), TCTTR (30 %), TNTTR (25 %), MHTKH (15 %), and five were identified in P. graminis (RKMTF (60 %), TKTTF, RKLTF, QKLTF, LHLPF (10 % each). Among P. striiformis isolates, three phenotypes were identified using the International and European sets of differentiating cultivars – 111E231 (88 %), 111E247 (6 %) and 78E199 (6 %). Using isogenic Avocet lines, 3 races were also identified, which differed among themselves in virulence to the Yr1, Yr11, Yr18 genes (with the prevalence of virulent ones (94 %)). Composite urediniums’ samples (a mixture of all identified races) of grass rust of each species were used to inoculate winter wheat cultivars. The most common winter wheat cultivars (75 %) were characterized by a resistant response when infected with P. graminis populations from common wheat and cereal grasses. All these cultivars were developed using donors of the rye translocation 1BL.1RS, in which the Lr26, Sr31, and Yr9 genes are localized. The number of winter wheat cultivars resistant to leaf rust in the seedling phase was lower (58 %). At the same time, all the studied cultivars in the seedling phase were susceptible to P. striiformis to varying degrees. The virulence analysis of the leaf, stem and stripe rust populations did not reveal significant differences in the virulence of the pathogens between wild-growing cereals and soft wheat. Urediniomaterial of all studied rust species successfully infested soft wheat cultivars. The results obtained indicate that grasses are rust infection reservoirs for common wheat crops in the North Caucasus.